A snapshot of guideline compliance reveals room for improvement: A survey of peripheral arterial catheter practices in Australian operating theatres. (26th September 2012) - Reynolds, Heather; Dulhunty, Joel; Tower, Marion; Taraporewalla, Kersi; Rickard, Claire
Abstract Aim To report a study in Australian operating theatres of compliance by the anaesthetic team with best peripheral arterial catheter practice for blood gas sampling and infection prevention. Comparisons are made with research recommendations and Centres for Disease Control Guidelines. Background There is wide global usage of peripheral arterial catheters in the operating theatre for haemodynamic monitoring and blood gas analysis. Frequent blood sampling from arterial catheters can lead to statistically significant blood loss and provide an infective potential. Evidence‐based research and clinical guidelines prescribe best practice. Design Cross‐sectional descriptive survey Methods Data were collected in 2009 from 64 major Australian hospitals using a self‐designed internet survey. Results/Findings Hand hygiene prior to catheter insertion was the only infection prevention practice entirely adherent with guidelines. The recommended ratio of discard to dead space volume of 2:1 to decrease unnecessary blood loss during blood gas sampling was reported by only 11 (17%) respondents. Less than 32 (50%) respondents used the preferred solution, chlorhexidine to disinfect the insertion site. Access ports were reported as 'never disinfected' before use by 30 (47%) respondents. Conclusion The complex operating theatre environment presents barriers, which contribute to non‐adherence with guidelines. These barriers need to be identified to plan strategies for improvement. A quality audit tool is proposed for development by nurses in collaboration with the anaesthetic team, providing a needed method to assess ongoing compliance with best peripheral arterial catheter care. Further international research would test the generalizability of our Australian findings.